PENERAPAN METODE PEMBELAJARAN COOPERATIVE TYPE G.I. UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR PADA KOMPETENSI DASAR MENGGUNAKAN ALAT-ALAT UKUR MEKANIK - Candra Adhi Nugroho; Pairun Roniwijaya (Jurnal Taman Vokasi, 2016)
This study aimed to know: (1) the learning achivement and (2) learning activeness in mechanic measuring tools subject through group investigation. The type of this study was an action research. Data collection techniques used tes, observation, and documentation. Data analysis techniques used decriptive analysis and quantitative to know the percentage of learning achivement and learning activeness in mechanic measuring tools subject through group investigation. This study shows that: (1) group discussion could improve learning activeness in mechanic measuring toosl subject. The percentage aberage of learning activeness in cycle I was 42.8%, cycle II was 80.67%, and cycle III was 92.02%: and (2) group discussion could improve learning achivement, the mean score of learning achivement in pre cycle was 52.06, cycle I was 66.62, cycle II was 75.59, and cycle III was 77.21.